Diversificação da avaliação em matemática nos anos finais do ensino fundamental para a promoção de uma aprendizagem efetiva - (:unkn) unknown (Universidade Federal de Goiás, 2019)
The evaluation is essential for the teaching-learning process and, beginning from this conception, it is necessary to study, reflect and analyze the evaluative practices. As evaluation is a great challenge for the majority of teachers and professionals who offer direct pedagogical support to the teaching profession, this theme must be studied and debated in order to make progress. In this way, the objective of this research was to investigate, apply and analyze how different means and instruments of evaluation adopted in two classes of the eighth grade of a municipal school in the state of Minas Gerais, contribute to the learning process of these students, in order to answer the following question: How can the diversification of means and instruments of evaluation in the classroom can contribute to improving the understanding of mathematics content? This study consists in the approach of a qualitative research, characterized by a Research-action. Data collection began in May 2018 and lasted until December of that year and was performed through a questionnaire, observation, oral and written interactions, application of evaluative activities in the classroom related to the content of mathematics in elementary school, conducting testing in phases and production of portfolios. For the analysis of the produced information, analysis bases and defined categories were created in the development of the research. The students understood the importance of this research, because they participated in a satisfactory way. Therefore, it was possible to verify that there was improvement in the learning of the developed contents and in the attitudes, which are essential in the experience in society. The research results highlight the possibilities of using diverse means and instruments of evaluation as a strategy to facilitate learning, may be used to guide public educational policies to encourage the training of teachers to carry out evaluations as a didactic tool.
Diversification of evaluation in mathematics in the final years of elementary school for the promotion of effective learning
Keywords: Avaliação da aprendizagem; Meios e instrumentos de avaliação; Ensino e aprendizagem; Evaluation of learning; Means and instruments of evaluation; Mathematics; Teaching-learning; Matemática; CIENCIAS EXATAS E DA TERRA::MATEMATICA